Low Shrinkage, Coarse‐Grained Tantalum–Alumina Refractory Composites via Cold Isostatic Pressing. Issue 8 (15th July 2022) - Endler, Dirk; Zienert, Tilo; Roungos, Vasileios; Hubálková, Jana; Gehre, Patrick; Aneziris, Christos G.
Abstract : Alumina–tantalum composites are produced in a two‐step synthesis via cold isostatic pressing (CIP) from commercially available raw materials without any addition of organic additives. The highest densification for fine‐grained composites is found with a maximum pressure of 150 MPa, whereby a cyclic pressure increase or at maximum pressure showed no measurable influence. The increase of the sintering temperature from 1600 to 1700 °C led to a higher densification up to a relative density of 75.8 % . Aggregates received by jawbreaking show a blocky morphology, rounded corners, and edges with porosities of 6.2 − 7.3 % . The formation of tantalum carbide and the incorporation of oxygen into the tantalum lattice are verified during sintering. The coarse‐grained composites produced from these aggregates show open porosities of 25.3 − 25.7 % and shrinkage < 0.5 % . Determined splitting tensile strenghts are in the range between 8.4 and 9.1 MPa. Abstract : Cold isostatic pressing (CIP) is used to produce fine‐ and coarse‐grained tantalum‐alumina composites. Different CIP regimes and various sintering temperatures are applied. The fine‐grained aggregates received via jawbreaking show a blocky morphology and porosities of 6.2–7.3%. The coarse‐grained composites produced by these aggregates show low shrinkage.